Quantitative trait loci and diferential gene expression analyses reveal the genetic basis for negatively associated beta‑carotene and starch content in hexaploid sweetpotato (Ipomoea batatas (L.) Lam) - Gemenet, D.; Silva Pereira, G. da; Boeck, B. de; Wood, J.C.; Mollinari, M.; Olukolu, B.A.; Díaz, F.; Mosquera, V.; Ssali, R.T.; David, M.; Kitavi, M.; Burgos, G.; et al. (Springer, 2020)
Thirteen fruits, eight legumes and three tubers consumed in the Andean regions of Ecuador were studied to determine their bioactive compounds, organic acids, sugars content, total antioxidant capacity, as well as to determine which among them showed the greatest contribution in terms of antioxidant activity and which compounds contributed to it. Among fruits, taxo fruits (Passiflora mollissima (Kunth) L.H. Bailey) presented the highest values of total phenolic, carotene content, and total antioxidant capacity. The ají ratón (Capsicum chinense Jacq) showed the highest content of vitamin C. Taxo showed the highest content of β carotene, whilst lycopene was identified only in guayaba fruits (Psidium guajava L.) and ají ratón was the principal source of lutein. In legumes, chocho perla (Lupinus mutabilis Sweet) showed the highest values for both total phenolic and flavonoid content, whilst frejol negro (Phaseolus vulgaris L.) and frejol canario (Vigna unguiculata (L.) Walp) showed the highest values for FRAP and DPPH assay, respectively. Between tubers, the jícama (Smallanthus sonchifolius (Poepp.) H. Rob.) had the majors values in terms of total phenolic, flavonoid content, and total antioxidant capacity. In terms of total antioxidant capacity, taxo fruits have the highest contribution in terms of total antioxidant capacity, whilst the dendogram shown the occurrence of five distinct groups in which taxo was located in the first largest group. Our data contributing towards gaining better knowledge about the Andean Ecuadorian diet and the composition of Andean food in order to estimate dietary intakes of health-promoting components.